Melanoma genomics – will we go beyond BRAF in clinics? - Justyna Mirek; Wiesław Bal; Magdalena Olbryt (Journal of Cancer Research and Clinical Oncology)
Abstract In the era of next-generation sequencing, the genetic background of cancer, including melanoma, appears to be thoroughly established. However, evaluating the oncogene BRAF mutation in codon V600 is still the only companion diagnostic genomic test commonly implemented in clinics for molecularly targeted treatment of advanced melanoma. Are we wasting the collected genomic data? Will we implement our current genomic knowledge of melanoma in clinics soon? This question is rather urgent because new therapeutic targets and biomarkers are needed to implement more personalized, patient-tailored therapy in clinics. Here, we provide an update on the molecular background of melanoma, including a description of four already established molecular subtypes: BRAF+, NRAS+, NF1+, and triple WT, as well as relatively new NGS-derived melanoma genes such as PREX2, ERBB4, PPP6C, FBXW7, PIK3CA, and IDH1. We also present a comparison of genomic profiles obtained in recent years with a focus on the most common melanoma genes. Finally, we propose our melanoma gene panel consisting of 22 genes that, in our opinion, are “must-have” genes in both melanoma-specific genomic tests and pan-cancer tests established to improve the treatment of melanoma further.